Chronic and Transient Poverty: Measurement and Estimation, with Evidence from China - Duclos, Jean-Yves; Araar, Abdelkrim; Giles, John (2012)
The paper contributes to the measurement of poverty and vulnerability in three ways. First, it proposes a new approach to separating poverty into chronic and transient components. Second, it provides corrections for the statistical biases introduced when using a small number of periods to estimate the importance of vulnerability and transient poverty. Third, it applies these tools to the measurement of chronic and transient poverty in China using a rich panel data set that extends over 17 years. Alternative measurement techniques are found to yield significantly different estimates of the relative importance of chronic and transient poverty. The precision of the estimates is also considerably enhanced by simple statistical corrections.